2016
DOI: 10.1007/s11999-016-4705-7
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic Voltage-controlled Electrical Stimulation Plus Prolonged Vancomycin Reduce Bacterial Burden of a Titanium Implant-associated Infection in a Rodent Model

Abstract: Background Cathodic voltage-controlled electrical stimulation (CVCES) of titanium implants, either alone or combined with a short course of vancomycin, has previously been shown to reduce the bone and implant bacterial burden in a rodent model of methicillin-resistant Staphylococcus aureus (MRSA) implant-associated infection (IAI). Clinically, the goal is to achieve complete eradication of the IAI; therefore, the rationale for the present study was to evaluate the antimicrobial effects of combining CVCES with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…A total of 12 adult Long‐Evans rats (males, 175–200 g/8–9 weeks) were acquired for the study. A previously described procedure was used to surgically place the AZ91 and cpTi implants . Following anesthesia administration using ketamine (50 mg/kg), xylazine (5 mg/kg), and acepromazine (1 mg/kg); the ventral periaxillary area was prepared by shaving, sterilizing with chlorhexidine and alcohol, and injection with local anesthetic (bupivacaine and lidocaine mix) subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 adult Long‐Evans rats (males, 175–200 g/8–9 weeks) were acquired for the study. A previously described procedure was used to surgically place the AZ91 and cpTi implants . Following anesthesia administration using ketamine (50 mg/kg), xylazine (5 mg/kg), and acepromazine (1 mg/kg); the ventral periaxillary area was prepared by shaving, sterilizing with chlorhexidine and alcohol, and injection with local anesthetic (bupivacaine and lidocaine mix) subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…A previously described procedure was used to surgically place the AZ91 and cpTi implants. 20,22,23 Following anesthesia administration using ketamine (50 mg/kg), xylazine (5 mg/kg), and acepromazine (1 mg/kg); the ventral periaxillary area was prepared by shaving, sterilizing with chlorhexidine and alcohol, and injection with local anesthetic (bupivacaine and lidocaine mix) subcutaneously. An oblique 1 cm skin incision was made over the shoulder joint, and sharp dissection through the subcutaneous fat and superficial muscle layers was carried down to expose the anterior portion of the rotator cuff [ Figure 1(A,B)].…”
Section: Antibacterial Effect In Vivomentioning
confidence: 99%
“…While the use of ES in wound care management is well established, we did not identify any previous studies assessing the impact of ES on wound biofilms in a human ex vivo model. Investigations of ES against biofilms in vivo are also sparse, with only six studies to date having assessed the effect of ES on biofilms, with the majority showing positive outcomes; however, none of these studies investigated the direct effect of ES on cutaneous wound bacterial biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have showed promising results for the application of cathodic DC electrical stimulation for the treatment of implant-associated infections in both in vitro and in vivo models (Canty, Luke-Marshall, Campagnari, & Ehrensberger, 2017;Ehrensberger et al, 2015;Nodzo et al, 2015Nodzo et al, , 2016. Despite these results, the specific mechanism of these antimicrobial effects is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%